2023
DOI: 10.3390/cells12060881
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ambient Temperature on Adipose Tissue Homeostasis, Metabolic Diseases and Cancers

Abstract: Adipose tissue is a recognized energy storage organ during excessive energy intake and an endocrine and thermoregulator, which interacts with other tissues to regulate systemic metabolism. Adipose tissue dysfunction is observed in most obese mouse models and humans. However, most studies using mouse models were conducted at room temperature (RT), where mice were chronically exposed to mild cold. In this condition, energy use is prioritized for thermogenesis to maintain body temperature in mice. It also leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 139 publications
0
3
0
1
Order By: Relevance
“…Typical room temperatures for housing mice can be considered mild cold conditions, whereas temperatures below 16°C are viewed as severe cold conditions, necessitating shivering thermogenesis. [12] To explore the effects of housing temperature on bone mass homeostasis, we employed micro-computed tomography (micro-CT) analysis to evaluate the bone structural features of SHAM and ovariectomized (OVX) mice, a commonly used primary osteoporosis model. After performing OVX and SHAM surgery on 8-week-old mice, the mice were maintained at 22°C, corresponding to standard room temperature housing conditions, and 30°C, corresponding to thermoneutral housing conditions, for 12 weeks, and the experiments were performed when the mice were 20 weeks old.…”
Section: Resultsmentioning
confidence: 99%
“…Typical room temperatures for housing mice can be considered mild cold conditions, whereas temperatures below 16°C are viewed as severe cold conditions, necessitating shivering thermogenesis. [12] To explore the effects of housing temperature on bone mass homeostasis, we employed micro-computed tomography (micro-CT) analysis to evaluate the bone structural features of SHAM and ovariectomized (OVX) mice, a commonly used primary osteoporosis model. After performing OVX and SHAM surgery on 8-week-old mice, the mice were maintained at 22°C, corresponding to standard room temperature housing conditions, and 30°C, corresponding to thermoneutral housing conditions, for 12 weeks, and the experiments were performed when the mice were 20 weeks old.…”
Section: Resultsmentioning
confidence: 99%
“…The use of thermoneutral housing modifies common physiological responses (e.g., heart rate, blood pressure, catecholamine release, basal metabolic rate) in mice [63]. In fact, the potential clinical relevance of such changes in modelling disease pathogenesis has been widely studied with strong success (e.g., cancer, asthma, allergy, inflammation, chronic stress) [68,90]. We have previously shown that the combination of HFD with thermoneutral housing (TN) creates a human-like DIO phenotype in male mice (e.g., induction of hepatic fibrosis [77], induction of atherosclerotic plaques [21], and discovery and recognition of rare immune cells that promote progression of MASLD [20]).…”
Section: Maternal Obesity Impacts Neonatal Offspring Health In Micementioning
confidence: 99%
“…Specifically, in comparison to TS, TN housing is associated with significant decreases in physiologic (e.g., basal heart rate and mean arterial blood pressure [65,66]) and metabolic (e.g., food intake and basal metabolic rate [67]) parameters and increases in inflammatory (e.g., serum cytokine levels [20]) parameters at the basal state. Notably, TN housing increases adipocyte size in murine inguinal white adipose tissue (iWAT) [68] and causes mouse brown adipose tissue (BAT) to closely resemble human BAT [69]. Such modulation of mouse physiology has allowed TN housing to improve mimicry of many human disease models, including cancer [64,[70][71][72][73], atherosclerosis [21,74], asthma [75], food allergy [76], and liver disease [77].…”
Section: Introductionmentioning
confidence: 99%
“…Os peptídeos natriuréticos participam de vários processos fisiológicos e essa ampla variedade de respostas é obtida a partir das ações distintas de peptídeos natriuréticos individuais taxa metabólica e a atividade termogênica são mínimas, mantida pelo metabolismo basal do animal (∼30°C para camundongos). No entanto, a grande maioria dos estudos presentes na literatura foi conduzida com camundongos em temperatura ambiente (∼22°C), sendo assim expostos cronicamente ao estresse pelo frio, temperatura confortável para humanos (Gordon, 1995;Ginting et al, 2023). A exposição crônica de animais a temperaturas inferiores a zona termoneutra leva à ativação de um processo neuro-endócrino sistêmico, chamado de termogênese adaptativa ou facultativa sem tremores.…”
Section: Expressão Gênica Dos Receptores De Peptídeos Natriuréticos N...unclassified